Teacher’s and students’ effort in overcoming the students’ speaking problems - Cut Damba Nabila; Bustami Usman; Hendra Heriansyah (Research in English and Education Journal, 2017)
Speaking is an interactive process of constructing meaning that involves producing, receiving and processing information. It means the information is included in speaking, people can get information about something they look for by speaking or communicating. However, learning English as a foreign language in fact is still a problematic thing for Indonesian students. This study was aimed at investigating the teacher’s and students’ efforts in overcoming the speaking problems at SMA Negeri 12 Banda Aceh. The research is intended to find out the speaking problems that the teacher’s and students’ faced through interview and document analysis. In order to investigate the efforts of the teacher and students in overcoming speaking problems in this study, the researcher uses qualitative study. The data were analyzed in accordance with Ali (2000) for the data of interview and Miles and Huberman (1984) for the data of document analysis. From the result of interview shows that there were 5 efforts (taking English course, reading English books, memorizing vocabularies, speaking English, and learning English in school) made by students in solving speaking problems and teacher’s effort was in increasing students vocabularies. Meanwhile, the result of document analysis shows that, the students got low score in speaking.